Ten new species of Meteorus (Hymenoptera: Braconidae) from Ecuador reared at the Yanayacu Biological Center for Creative Studies - Jones, Guinevere Z.; Shaw, Scott R. (Zootaxa, 2012)
Ten new species of the braconid genus Meteorus are described, along with biological information. Specimens were reared from lepidopteran larvae collected in the northeastern Andes of Ecuador, a hotspot of global diversity. The new species described and illustrated are: M. bustamanteorum, M. caritatis, M. horologium, M. imaginatus, M. luteus, M. margarita, M. oreo, M. porcatus, M. quasifabatus, and M. zitaniae. The biology of these species has also been observed: reared as single wasp emergences are M. caritatis, M. imaginatus, M. luteus, and M. oreo. The majority of the descriptions are of gregarious wasp rearings, which occur within M. bustamanteorum, M. horologium, M. margarita, M. porcatus, M. quasifabatus, and M. zitaniae. There is a large diversity of taxa used for oviposition; four species were reared from Arctiidae caterpillars, two from Nymphalidae, and one each from Apatelodidae, Limacodidae, Megalopygidae, and Noctuidae. The host data for the new species of Meteorus shows a strong correlation between type of host defense and whether development yields a solitary or gregarious wasp. All of the Meteorus wasps collected from this region have been new species, which highlights the enormous biodiversity and importance of describing new species in the neotropics.